A massive freshwater mussel bed (Bivalvia: Unionidae) in a small river in Ukraine - Protasov, Alexander (2015)
During a monitoring survey, a massive mussel bed was found and studied in the Gnily Rig River, Ukraine. The mussel bed was 25 cm thick and multilayered, with one of the greatest densities and biomass (wet weight) recorded so far in natural aggregations: up to 1,801.0 ± 175.4 ind./m² and up to 88.3 ± 20.7 kg/m², respectively. The site was surveyed periodically since 2009, and despite the temporal differences in the density (but not in biomass) the mussel bed was stable and should be considered for protection due to its high ecological and conservational value.